Graphene Doped with Transition Metal Oxides: Enhancement of Anode Performance in Lithium-Ion Batteries - Jun Du; Liwei Liao; Binbin Jin; Xinyi Shen; Zhe Mei; Qingcheng Du; Hailin Nong; Bingxin Lei; Liying Liang (Metals)
In recent years, transition metal oxides (TMOs) have emerged as promising candidates for anode materials in lithium-ion batteries (LIBs) owing to their high theoretical capacities. Regrettably, most TMOs exhibit poor electronic/ionic conductivity and undergo substantial volume expansion during the lithiation/delithiation processes. In this study, an electrostatic spinning method using polyacrylonitrile, graphene, and iron(III) acetylacetonate as precursors was employed to synthesize the Fe3O4@G/C composite through carbon coating and graphene doping. The composition, phase structure, and morphology of the Fe3O4@G/C composite were thoroughly investigated. The electrochemical performance of the Fe3O4@G/C composite as a lithium-ion battery anode was evaluated through a continuous charge–discharge cycling test. After 100 cycles at a current density of 0.1 A/g, the specific capacity of the Fe3O4@G/C material remained at 595.8 mAh/g. Additionally, the incorporation of graphene leads to a reduction in the electron orbital energy of Fe, which was verified by comparing the density of states (DOS) before and after the doping. Simultaneously, the electrochemical performance of CoO@G/C and NiO@G/C composites further demonstrates that doping transition metal oxides with graphene can enhance their performance as anodes for lithium-ion batteries. We anticipate that this design concept will open new avenues for the development of transition metal oxides (TMOs) and propel their adoption in practical applications.